Adaptation As Precaution. (1st April 2014) - Hartzell-Nichols, Lauren
Abstract : Precaution is usually associated with the intuition that it is better to be safe than sorry, and/or that it is sometimes necessary to act in advance of scientific certainty to prevent harmful outcomes. At this point, we cannot entirely prevent climate change, but we can affect how harmful such change is. Adaptation may therefore be understood as a precautionary measure against the damage due to climate change. 'The' precautionary principle alone is too vague to shape adaptation policy, but a limited catastrophic precautionary principle may productively guide adaptation policy makers. I argue in this paper that an explicit commitment to a precautionary approach based on the catastrophic precautionary principle could and should be made to strengthen the adaptation policies introduced at the United Nations Framework Convention on Climate Change (UNFCCC).